Family, church, and market : a Mennonite community in the Old and the New Worlds, 1850-1930 - Loewen, Royden, 1954- (Heritage., 1993)
Royden Loewen's account tells of three generations of Mennonites for whom the farm family was the primary social unit. The sectarian, lay-oriented church congregation interpreted life's meaning and enforced strict social boundaries on the community level.